Tree rings provide no evidence of a CO2 fertilization effect in old‐growth subalpine forests of western Canada. (1st February 2019) - Hararuk, Oleksandra; Campbell, Elizabeth M.; Antos, Joseph A.; Parish, Roberta
Abstract: Atmospheric CO2 concentrations are now 1.7 times higher than the preindustrial values. Although photosynthetic rates are hypothesized to increase in response to rising atmospheric CO2 concentrations, results from in situ experiments are inconsistent in supporting a CO2 fertilization effect of tree growth. Tree‐ring data provide a historical record of tree‐level productivity that can be used to evaluate long‐term responses of tree growth. We use tree‐ring data from old‐growth, subalpine forests of western Canada that have not had a stand‐replacing disturbance for hundreds of years to determine if growth has increased over 19th and 20th centuries. Our sample consisted of 5, 858 trees belonging to five species distributed over two sites in the coastal zone and two in the continental climate of the interior. We calculated annual increments in tree basal area, adjusted these increments for tree size and age, and tested whether there was a detectable temporal trend in tree growth over the 19th and 20th centuries. We found a similar pattern in 20th century growth trends among all species at all sites. Growth during the 19th century was mostly stable or increasing, with the exception of one of the coastal sites, where tree growth was slightly decreasing; whereas growth during the 20th century consistently decreased. The unexpected decrease in growth during the 20th century indicates that there was no CO2 fertilization effect on photosynthesis. We compared the growth trends from our four sites to the trends simulated by seven Earth System Models, and saw that most of the models did not predict these growth declines. Overall, our results indicate that these old‐growth forests are unlikely to increase their carbon storage capacity in response to rising atmospheric CO2, and thus are unlikely to contribute substantially to offsetting future carbon emissions. Abstract : Atmospheric carbon dioxide (CO2 ) concentrations are now 1.7 times higher than the preindustrial values. CO2 is often considered a limiting factor for plant growth, which means that an increase in atmospheric CO2 levels should stimulate plant growth rates. We tested this hypothesis by analyzing historical tree‐level productivity calculated using tree‐ring data from old‐growth subalpine forests of western Canada. Once the effects of tree size and age were removed, we observed an increase in tree growth throughout the 19th century, but the trajectory was reversed in the 20th century, suggesting that CO2 was not stimulating tree growth in the 20th century.